2010
DOI: 10.1090/conm/517/10144
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Koch snowflake fractal billiard: computer experiments and mathematical conjectures

Abstract: In this paper, we attempt to define and understand the orbits of the Koch snowflake fractal billiard KS. This is a priori a very difficult problem because ∂(KS), the snowflake curve boundary of KS, is nowhere differentiable, making it impossible to apply the usual law of reflection at any point of the boundary of the billiard table. Consequently, we view the prefractal billiards KSn (naturally approximating KS from the inside) as rational polygonal billiards and examine the corresponding flat surfaces of KSn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…We have shown that in the case of Ω(KS), Ω(T ) and Ω(S a ), we can determine a sequence of compatible periodic orbits. We will see that in each case of a fractal billiard, under certain conditions, a sequence of compatible periodic orbits (or a proper subset of points from each footprint F n (x 0 n , θ 0 n )) will converge to a set which can be thought of as a true orbit of a fractal billiard table (or such a sequence will yield a subsequence of basepoints converging to what we are calling an elusive point in [LapNie2,LapNie3]). …”
Section: Fractal Billiardsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that in the case of Ω(KS), Ω(T ) and Ω(S a ), we can determine a sequence of compatible periodic orbits. We will see that in each case of a fractal billiard, under certain conditions, a sequence of compatible periodic orbits (or a proper subset of points from each footprint F n (x 0 n , θ 0 n )) will converge to a set which can be thought of as a true orbit of a fractal billiard table (or such a sequence will yield a subsequence of basepoints converging to what we are calling an elusive point in [LapNie2,LapNie3]). …”
Section: Fractal Billiardsmentioning
confidence: 99%
“…This paper constitutes a survey of a collection of results from [LapNie1,LapNie2,LapNie3] as well as the announcement of new results on the T -fractal billiard table Ω(T ) (see [LapNie6]) and a self-similar Sierpinski carpet billiard table Ω(S a ) (see [CheNie]). …”
mentioning
confidence: 99%
“…In [CheNie1], the fractal billiard table is a self-similar Sierpinski carpet billiard table. In [LapNie1,LapNie2,LapNie3], the fractal billiard table under consideration was the Koch snowflake fractal billiard table. In [LapNie4], recent results on the Koch snowflake fractal billiard table and a self-similar Sierpinski fractal billiard table are surveyed and the T -fractal billiard table is introduced; preliminary results regarding the T -fractal billiard table were presented without proof.…”
Section: Introductionmentioning
confidence: 99%
“…For the reader's easy reference, we provide in this section various definitions appearing in previous joint works; see [CheNie1,LapNie1,LapNie2,LapNie3,LapNie4]. However, the notation in all of the definitions will reflect the fact that we are discussing the T -fractal billiard table, which will significantly simplify the exposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation